Self-organized mobile communication technologies and techniques for network optimization - Diab, Ali (Advances in wireless technologies and telecommunication (AWTT) book series, 2016)
This book explores self-organizing networks (SONs) as a proposed solution for the automation of mobile communication tasks that currently require significant efforts for planning, operation, and management, emphasizing research on the latest generation of mobile communication networks, the 5th generation (5G).